History of controlled trials in medicine: real priorities are little-known. Report 1. Basic concepts, terms, and disciplines that use medical experiment: historical and philosophical sources - A. N. Koterov; O. A. Tikhonova; L. N. Ushenkova; A. P. Biryukov (Фармакоэкономика, 2021)
The three-report review was aimed at describing the historical development of clinical trials, controlled trials (CT) and randomized controlled trials (RCT), and the inclusion of these experimental approaches in disciplines related to both the health of individuals and populations (medicine and epidemiology). In Report 1, the authors consider the terminology issues applied to CT and RCT, the sources of the involved concepts, and relevant disciplines. It was shown that the terms ‘control’ and ‘trial’ appeared in experimental literature only at the end of the 19th century, ‘CT’ appeared in the first third or quarter of the 20th century, and the term ‘RCT’ appeared only in 2000s. It was found that approaches with CT and RCT were often included even in classical epidemiology, and this fact eliminates the specificity of differences between observational and experimental disciplines and blurred the difference between inductive and deductive methodologies. Scientific, philosophical, conceptual, and historical aspects were also considered for three areas that included CT and RCT: epidemiology, clinical epidemiology and evidence-based medicine (EBM). It was concluded that classical epidemiology, using predominantly inductive approaches, was not the scope of real medical experiments, in the first place, and, secondly, its prognosis was not aimed at the individual. At the same time, both clinical epidemiology and EBM, which mainly use deductive approaches, involve experiments, making it possible to make prognosis for a particular patient. The proposed summarizing scheme of the historical origins and philosophical foundations of disciplines aimed at finding and proving health effects using observational and experimental approaches reflects the problems considered and covers individual time milestones, which, as a rule, are not named in modern epidemiology textbooks and textbooks of other disciplines.